The effect of insect activity on clothing damage evidence following a period of decomposition - Esta Bostock; Gareth Parkes; Graham Williams (Crime, Security and Society, 2019)
Clothing damage analysis is a field in which the examination of stab cuts to clothing can reveal information about the stabbing implement and the actions used to cause such damage. This is particularly useful where the victim of the stabbing is still alive or when the deceased is in an advanced state of decomposition. In both situations, wound examination would not be useful due to the evidence being compromised by natural processes. In cases where the body is severely decomposed, the clothing can be the only source of evidence remaining; however, it is possible that insect activity may compromise any stab cuts that may be present. This study recreates the effect that a decomposing body might have on any fabric, by wrapping the damaged cotton fabric around meat, and allowing the meat to decompose for two weeks. The following factors were explored; the presence/absence of blood on the edges of the damage; and whether the stab cut is exposed to the air or is face-down in the soil. It was observed that after one week, the edges of the stab cuts were worn with the effect being enhanced after two weeks. It was also observed that the presence of blood increased the amount of wear, as did the presence of meat. The visual observations were also supported by measuring the depth of fraying of the edges of the stab cuts.